A simple goiter of the right ventricle: case report and literature review - Luo, Shuai; Tian, Xiaoxue; Xu, Ting; Wang, Jinjing (Frontiers in Cardiovascular Medicine, 2024)
BackgroundCardiac teratoma is extremely rare, accounting for less than 1% of adult cardiac tumors. These teratomas typically occur in the pericardium and myocardium, with intracardiac teratomas being even rarer. Given the limited number of cases, diagnosing and treating intracardiac teratomas remains challenging.Case demonstrationA 50-year-old man was admitted to the hospital with a 1-month history of chest tightness and shortness of breath after exertion. Color Doppler echocardiography revealed a hyperechoic mass of approximately 58 mm in diameter in the right ventricular cavity and outflow tract. Postoperative pathological examination confirmed a right ventricular monodermal teratoma (goiter). The patient was followed up for 2 years with good overall health and no recurrence.ConclusionsIntracardiac teratomas are exceedingly uncommon tumors, with the predominant right ventricle involvement being observed across a wide age range. These teratomas are often histologically classified as benign. The early detection of intracardiac teratomas relies on imaging findings, while a definitive diagnosis requires histopathological examination. The primary treatment is surgical resection, which yields a favorable prognosis.